Penambahan sr pada aluminium paduan a356 dengan metode lost foam casting (lfc) - Suherman Suherman; Abdan Syakura; Ilmi Ilmi; Amirsyam Amirsyam (University of Muhammadiyah Jakarta, 2022)
The casting process and cooling rate determine the morphology of the authentic silicon particles produced in aluminum alloys. The slow cooling rate of aluminum alloy through the Lost Foam Casting (LFC) method a result of low mechanical properties. The purpose of this study was the effect of added Strontium (Sr) modifier to aluminum A356 on the microstructure and mechanical properties of the LFC method. The Aluminum A356 alloys are melted using a crucible and poured at a temperature of 730 oC on the surface of the polystyrene pattern which has been coated with refractory materials. The addition of the Strontium modifier was studied for its effect on changes in microstructure and mechanical properties (hardness, impact strength, and tensile strength). The results of this study indicate a change in the authentic silicon particles from an acicular to a filamentous form. The value of hardness, maximum tensile strength, and impact strength on the castings increased after the addition of Sr modifier to aluminum alloy A356.